Implantação de um condomínio sustentável na cidade de Porto Velho - Rondônia - Rech, Lucas da Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
This work deals with the theme of sustainable construction, including the application of ecotechnics in civil construction, such as the generation of photovoltaic energy, capture and use of rainwater and sewage treatment. The objective of the work is the construction of a condominium, in the city of Porto Velho, state of Rondônia. The condominium consists of 10 (ten) houses that present water collection systems, the system allows the use of water for non-potable purposes. On the roof were used ecological tiles, which have a lower cost and also improve thermal comfort in the residence. For the catchment system was considered the system in loco, that uses ecological fossa in the common area of the condominium. In addition to these, other ecotechniques and materials that cause a lower environmental impact were studied, not being all inserted in the project due to the costs involved. In each item considered in the project, budgets were made with external companies to enable a cost analysis. At the end of the project, it was concluded that ecotechnics and materials, although most of them still have higher values than normal ones, present other advantages than economic ones

Este trabalho aborda o tema de construções sustentáveis, englobando a aplicação de ecotécnicas na construção civil, como a geração de energia fotovoltaica, captação e aproveitamento de água de chuva e tratamento de esgoto. O objetivo do trabalho é a construção de um condomínio, na cidade de Porto Velho, no estado de Rondônia. O condomínio é composto por 10 (dez) casas que apresentam sistemas de captação de água, o sistema possibilita a utilização da água para fins não potáveis. No telhado foram utilizadas telhas ecológicas, que possuem um menor custo e também melhoram o conforto térmico na residência. Para o sistema de captação foi considerado o sistema in loco, que utiliza fossa ecológica na área comum do condomínio. Além dessas, foram estudadas outras ecotécnicas e materiais que causassem um menor impacto ambiental, não sendo todos inseridos no projeto devido aos custos envolvidos. Em cada item considerado no projeto foram feitos orçamentos com empresas externas para que possibilitasse uma análise de custo. Ao final do projeto concluiu-se que as ecotécnicas e materiais, embora em sua maioria ainda possuam valores maiores que os normais utilizados, apresentam outras vantagens que não só as econômicas
Implantation of a sustainable condominium in the city of Porto Velho - Rondônia
Keywords: Arquitetura sustentável; Eficiência do uso da água; Energia solar; Construção civil; Sustainable architecture